Rancangan Pedoman Akuntansi dan Standar Operasional Prosedur (SOP) Penerimaan dan Pengeluaran Kas pada Taman Kanak-Kanak Cahaya Mutiara - Sidabutar, Joy Darlene; Khairunnisa, Hera; Nasution, Hafifah (LPPM Universitas Negeri Jakarta, 2025)
Designing an accounting guidelines and standard operating procedures (SOP) pertaining to cash receipts and expenditures at TK Cahaya Mutiara is the aim of this study. The researcher uses a qualitative method with a case study approach and the ADDIE development model for accomplishing the goals of this study. This study used interviews, documentation, and observation, as data collection methods. Data reduction, data presentation, and conclusion drawing are all used in the data analysis techniques. This research produced a design of Accounting Guidelines that contains various information related to financial recording. In the meantime, the SOP includes the work steps associated with the entity's cash inflow and outflow procedure in accordance with the internal control concept. The outcomes of the product's evaluation and socialization at the school showed that both items are useful for the entity's future use. Future researchers are advised to implement, evaluate, and possibly improve the products.